O Arduino como recurso didático para o ensino de resistores - Ferreira, Ricardo Vanjura (2020)
In recent decades, social relations have been profoundly altered with the arrival of information and communication technologies. The internet era has made it possible for human beings to shorten distances, optimize time and share information like never before. Faced with this new era, there are great pedagogical opportunities for teaching Physics, among them, the visual and interactive approach to physical concepts relevant to teaching practice, but which are difficult to be learned by the student. In this sense, computational modeling linked to the theory proposed in textbooks, combined with different instructional materials, allows an interpretation of various phenomena in a simple and easy way. In this sense, this work is based on the development of a Teaching-Learning Sequence as an alternative for teaching electrical resistors in high school. For that, we used the Arduino platform and programming resources to develop a script with computational commands (programming) capable of reading and graphing the studied devices, allowing students to visualize such phenomena.